Konstipasi fungsional pada anak - Herlina Loka; Atan Baas Sinuhaji; Supriatmo dr; Ade Rachmat Yudiyanto (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Constipation and gastroesophageal reflux are commonly found in the childhood. Delayed colonic transit time in children with functional constipation made the children experience gastroesophageal reflux symptoms such as regurgitation, vomiting, acid regurgitation, pyrosis, hiccup, belching, difficulty in swallowing and chronic cough.Keywords: gastro esophageal reflux; constipation; regurgitation; children